Assessing adherence to antiretroviral therapy in randomized HIV clinical trials: a review of currently used methods. Issue 3 (March 2013) - Marcellin, Fabienne; Spire, Bruno; Carrieri, Maria Patrizia; Roux, Perrine
Antiretroviral therapy for the treatment of HIV infection requires high levels of adherence to both maintain plasma HIV RNA at undetectable levels and prevent the emergence of drug resistance. As adherence to treatment is a major criterion for the evaluation of therapeutic outcomes, randomized clinical trials (RCTs) conducted among HIV-infected patients commonly include an assessment of adherence. However, there is still no gold-standard tool for assessing adherence behaviors in HIV RCTs. The methods currently used to collect and analyze adherence data are varied, which makes the comparison of results between studies difficult. The scope of this article is to review and discuss the range of adherence measures currently used in RCTs conducted among HIV-infected adults.